Software Testing in the Indonesian Industry: Survey of Methods, Tools, and Documentation - Maspupah, Asri; Rahmani, Ani; Min, Joe Lian; Roshinta, Trisna Ari (Department of Informatics, Siliwangi University, Indonesia, 2024)
Software testing plays a crucial role in the software development by ensuring that software is accurate and of high quality. Many software companies neglect software testing, which can lead to unprofitable business outcomes. For example, ineffective software testing may fail to identify all defects, resulting in increased development costs. A key factor determining the success of software testing is the strategy for implementing the testing process, the selection of testing tools, and the documentation of testing activities. This article examines the current state of software testing processes in the Indonesian software industry. The research objective is to analyze the software testing implementation strategy within the software development context, focusing on three main areas: software testing methodology, software testing tools, and software testing documentation. The research employs a survey method, collecting data from several respondents, Indonesian software companies, via an online questionnaire. The research findings indicate that testing is still predominantly manual. However, some software companies have begun to adopt a combination of manual and automated testing. Most companies utilize software testing documentation for reporting purposes during the execution of tests. Nevertheless, documenting test cases as a guide for testing execution is not prioritized as highly as bug reporting. Conversely, many Indonesian software companies have adopted testing tools and conducted performance testing to ensure software quality. Consequently, the software testing process in the Indonesian software industry tends to adhere to formal methods in accordance with the ISO/IEC/IEEE 29119 software testing standards